Process-based information systems: a component-based systems development infrastructure - Pereira, José Luís Mota (2014)
Owing to the highly competitive business environment in which todays organizations have to operate, a quick and effective way of developing and maintaining their information systems is of utmost importance to their success. Obviously, the computerized information systems that support the everyday operations and management of organizations play a critical role in their competitiveness. In this paper we describe a specific architectural solution, largely built on the functionalities provided by collaborative/workflow technologies, which will facilitate the development of distributed systems in a component based fashion. Moreover, we demonstrate that this specific kind of distributed system allows organizations to evolve quickly in face of changing business requirements, and facilitates the integration of the existing and new technologies, simplifying the overall development and maintenance effort of information systems.